2022
DOI: 10.1249/jes.0000000000000290
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Exercise-Induced Cardiac Remodeling Differ Between Young and Aged Hearts

Abstract: Exercise is cardioprotective via distinct mechanisms in aged and young hearts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…For male rats on a high-fat diet, 12 weeks of running exercise (60 min per session, five sessions per week) was associated with higher SOD1 levels in the aorta and mesenteric artery, relative to those in the non-exercise group [ 76 ]. In a human study, it has been reported that exercise training is effective in restoring the function and structure of the heart and blood vessels with the increase in SOD1 levels [ 77 ]. Recent reports indicating that resistance training is less effective than aerobic training in activating antioxidative function [ 78 , 79 ] support the use of dynamic-resistance exercise, such as in our study, for restoring antioxidative function.…”
Section: Discussionmentioning
confidence: 99%
“…For male rats on a high-fat diet, 12 weeks of running exercise (60 min per session, five sessions per week) was associated with higher SOD1 levels in the aorta and mesenteric artery, relative to those in the non-exercise group [ 76 ]. In a human study, it has been reported that exercise training is effective in restoring the function and structure of the heart and blood vessels with the increase in SOD1 levels [ 77 ]. Recent reports indicating that resistance training is less effective than aerobic training in activating antioxidative function [ 78 , 79 ] support the use of dynamic-resistance exercise, such as in our study, for restoring antioxidative function.…”
Section: Discussionmentioning
confidence: 99%